RETRACTED: Mitochondrial-Associated Protein LRPPRC is Related With Poor Prognosis Potentially and Exerts as an Oncogene Via Maintaining Mitochondrial Function in Pancreatic Cancer - Wang, Li; Luo, Jun; Li, Yuchen; Lu, Yanrong; Zhang, Yi; Tian, Bole; Zhao, Ziyi; Hu, Qiong-ying (Frontiers in Genetics, 2022)
Background The mitochondrial-associated protein LRPPRC exerts multiple functions involved in physiological processes, including mitochondrial gene translation, cell cycle progression and tumorigenesis. Previously, LRPPRC was reported to regulate mitophagy by interacting with Bcl-2 and Beclin 1 and thus modifying the activation of PI3KCIII and autophagy. Considering that LRPPRC was found to be negatively associated with survival rate, we hypothesize that LRPPRC may be involved in pancreatic cancer progression via its regulation of autophagy. Methods real-time quantitative PCR was performed to detect the expression of LRPPRC in 90 paired pancreatic cancer and adjacent tissues and five pancreatic cancer cell lines. Mitochondrial reactive oxidative species (ROS) level and function were measured. Mitophagy was measured by performing to detect LC3 level. Results By performing RT-qPCR, the association of LRPPRC with the prognosis of pancreatic cancer was established and pancreatic cancer tissues had significantly higher LRPPRC expression than adjacent tissues. LRPPRC was negatively associated with the overall survival rate. LRPPRC was also upregulated in pancreatic cancer cell lines. Knockdown of LRPPRC promoted ROS accumulation, decreased mitochondrial membrane potential (MMP), promoted autophagy/mitophagy, and induced mitochondrial dysfunction. Subsequently, knockdown of LRPPRC inhibited malignant behaviors in PANC-1 cells, including proliferation, migration, invasion, tumor formation and chemoresistance to gemcitabine. Finally, by inhibiting autophagy/mitophagy using 3-MA, the inhibitory effect of LRPPRC knockdown on proliferation was reversed. Conclusion Taken together, our results indicate that LRPPRC may act as an oncogene via maintaining mitochondrial homoeostasis and could be used as a predictive marker for patient prognosis in pancreatic cancer.